Assessing the Impact of the 2012 National Student Loan Forgiveness on Rural Health Human Resources - Michel Grignon; Qian Liu; Yihong Bai; Balqis Etoom (McMaster University Library Press, 2024)
On 1 January 2013, the federal Canada Student Financial Assistance Program (then known as the Canadian Student Loan Program) granted loan forgiveness to family physicians or nurses working at least 400 hours a year in a "rural" area of Canada. This is a return-for-service (RFS) program forgiving a maximum amount of the loan for each year worked in a designated area, up to a maximum of five years. The goal of the policy was to attract more family physicians and nurses to underserved areas and address the inequality in health between rural and urban areas in the country. The policy was accepted on principle but raised issues of non-compatibility between the federal and provincial RFS to attract health care workers to underserved areas, in particular its blanket definition of those areas as "rural," whereas provincial programs use criteria based on the density of physicians or nurses per population. Le 1er janvier 2013, le Programme canadien d'aide financière aux étudiants (connu à l'époque sous le nom de Programme canadien de prêts étudiants), a accordé une exonération aux médecins de famille et personnels infirmiers travaillant au moins 400 heures par an dans une région « rurale » du Canada. Il s'agit d'une d'obligation de retour de service (RDS) exonérant d'un montant maximum du prêt pour chaque année travaillée dans une région désignée, pour un maximum de cinq ans. L'objectif de cette politique était d'attirer davantage de médecins de famille et de personnels infirmiers dans les régions mal desservies et de remédier à l'inégalité de santé entre les zones rurales et urbaines du pays. La politique a été acceptée sur le principe, mais a soulevé des questions d'incompatibilité entre les RDS provinciaux et fédéraux visant à attirer des personnels infirmiers dans les zones mal desservies, en particulier sa définition générale des zones comme « rurales », alors que les programmes provinciaux utilisent des critères basés sur la densité de médecins ou de personnels infirmiers par rapport à la population.